2017
DOI: 10.25159/1727-7140/1807
|View full text |Cite
|
Sign up to set email alerts
|

Creating Sustainable Community Structures for Reintegrated Liberian Child Soldiers: Part I

Abstract: This article deals with the socio-political context of the Liberian civil war. It gives background to the conflict, explains how the different factions emerged and how they involved children in the conflict to be reintegrated afterwards. It examines how different community structures are identified during the reintegration processes of child soldiers and questions whether the right structures are identified. To address these issues, the question is asked: What international and regional efforts and policies we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Their study revealed that their families and communities had rejected 90% of the "bush wives." Many of the women ex-combatants who return home to families and communities experience high levels of abuse (Ferreira & Stuart Muttiti, 2016). Solomon and Ginifer (2008) concluded that the community response to fear, denial, discrimination, and stigma have accompanied females associated with armed conflicts.…”
Section: Reintegration Experiencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Their study revealed that their families and communities had rejected 90% of the "bush wives." Many of the women ex-combatants who return home to families and communities experience high levels of abuse (Ferreira & Stuart Muttiti, 2016). Solomon and Ginifer (2008) concluded that the community response to fear, denial, discrimination, and stigma have accompanied females associated with armed conflicts.…”
Section: Reintegration Experiencesmentioning
confidence: 99%
“…Although the reintegration program sought to provide ex-combatants, including ex-child soldiers, with educational opportunities, computer training, and vocational skills training (Kaplan & Nussio, 2018;McMullin, 2013a; United Nations, DDR Resource Centre, 2020), it received heavy criticism. Like DDR programs in Somalia, Liberia's DDR program has been condemned as ineffective because of its vague mandate, lack of funding (Ferreira & Stuart Muttiti, 2016;Zena, 2013;UNICEF, 2009), and lack of research (Hanson, 2007). Similar findings point to inadequate and untimely reintegration opportunities, discontinuity in funding (Awodola, 2012), the lack of reliable data, and the use of money to incentivize ex-child soldiers' participation (Palmer, 2006).…”
Section: Reintegration Experiencesmentioning
confidence: 99%